2014
DOI: 10.1016/j.micpath.2014.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Porcine intestinal glycosphingolipids recognized by F6-fimbriated enterotoxigenic Escherichia coli

Abstract: One important virulence factor of enterotoxigenic Escherichia coli is their ability to adhere via fimbrial adhesins to specific receptors located on the intestinal mucosa. Here, the potential glycosphingolipid receptors of enterotoxigenic F6-fimbriated E. coli were examined by binding of purified F6 fimbriae, and F6-expressing bacteria, to glycosphingolipids on thin-layer chromatograms. When intestinal mucosal non-acid glycosphingolipids from single pigs were assayed for F6 binding capacity, a selective intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The presence of an additional hydroxyl group in the lipid moiety of a GSL seems important for the pathogenesis of bacterial infections and in particular for intestinal colonization of pathogens, since ceramide hydroxylation of GSL receptor molecules might play a functional role in increasing toxin affinity towards GSL receptors as shown for binding of Stxs to Gb3Cer [45]. Furthermore, hydroxylation of the ceramide moiety may exert a reinforcing effect for host-pathogen interaction suggesting an advantage for certain pathogens as shown for F4- and F6-fimbriated enterotoxigenic E. coli in adhesion studies with porcine intestinal GSLs [46,47] and F1C-fimbriated uropathogenic E. coli [48]. …”
Section: Discussionmentioning
confidence: 99%
“…The presence of an additional hydroxyl group in the lipid moiety of a GSL seems important for the pathogenesis of bacterial infections and in particular for intestinal colonization of pathogens, since ceramide hydroxylation of GSL receptor molecules might play a functional role in increasing toxin affinity towards GSL receptors as shown for binding of Stxs to Gb3Cer [45]. Furthermore, hydroxylation of the ceramide moiety may exert a reinforcing effect for host-pathogen interaction suggesting an advantage for certain pathogens as shown for F4- and F6-fimbriated enterotoxigenic E. coli in adhesion studies with porcine intestinal GSLs [46,47] and F1C-fimbriated uropathogenic E. coli [48]. …”
Section: Discussionmentioning
confidence: 99%
“…Studies on the F6 receptors suggested that intestinal brush border receptors, particularly sulfatide, are released in the mucus of post-neonatal pigs inhibiting fimbriae-mediated adhesion and colonization (141–143). Lactotetraosylceramide, which was recently detected as a carbohydrate receptor moiety, was suggested to be inactivated by fucosylation in older pigs (144). In contrast, the adhesion and colonization by F18-fimbriated ETEC isolates was proposed to be dependent on receptors that develop progressively with age during the first 3 weeks after birth (145).…”
Section: Adhesins and Host Receptorsmentioning
confidence: 99%
“…In addition to the two entero-adhesive properties of FasG, a third type of F6 binding occurs between the major subunit FasA and piglet brush border hydroxylated ceramide monohexoside (165). More recently, F6 fimbriae were shown to bind to lactotriaosylceramide and lactotetraosylceramide isolated from the intestines of 6 weeks old pigs (144). Whether these receptors are already expressed in younger neonatal piglets, which are the targets for F6-fimbriated ETEC, was not determined.…”
Section: Adhesins and Host Receptorsmentioning
confidence: 99%
“…GSLs are attachment sites for a huge number of bacteria and viruses as well as targets for bacterial toxins (22)(23)(24)(25)(26). Plasma membrane segregation into microdomains is well recognized as a functional requirement for binding of pathogens and toxins to gain entry into cells (27)(28)(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%